Role of Digital Health in FGIDs, A Mini Review - Issariyakulkarn, Navapan (Asian Medical Journal and Alternative Medicine, 2024)
Treating functional GI disorders (FGIDs) caused by abnormal gut-brain interactions requires an understanding of individual GI pathophysiology as well as the patient’s behaviors. Many physicians frequently struggle to manage these patients due to a lack of knowledge regarding the patient’s pathophysiology and behaviors. Many digital tools for collecting and recording patients’ health information, which also include patient communication, are available to assist the physician in better understanding the patient. The purpose of this review is to assess how digital health can help FGIDs treatment and the interpretation of GI physiology testing.